Short Communication: Cremanthodium indica (Asteraceae, Senecioneae), a new species from the Eastern Himalaya, India - Dipankar Borah; Rajeev Kumar Singh; Lobsang Tashi Thungon (Society for Indonesian Biodiversity, 2021)
Abstract. Borah D, Singh RK, Thungon LT. 2021. Short Communication: Cremanthodium indica (Asteraceae, Senecioneae), a new species from the Eastern Himalaya, India. Biodiversitas 22: 1268-1272. Cremanthodium indica D.Borah, R.Kr. Singh & Thungon (Asteraceae, Senecioneae), a new species from Eastern Himalayan state Arunachal Pradesh, India is described and illustrated. The new species is allied to Cremanthodium nobile (Franch.) Diels ex H.Lév. in having elliptic-obovate basal leaves, solitary, nodding capitula and hemispheric involucre, but differs by densely pale yellow tomentose stem, stem leaves 5–9, 1.6–2.1 cm distant, outer phyllaries 2.3–2.8 mm wide, inner phyllaries elliptic, 3–5 mm wide, apex acute, ray lamina creamy, oblong, 2–2.3 cm long, apex truncate, distinctly 3-dentate, ray tube 1.5–2 mm long, tubular florets creamy, 8–9 mm long and pappus 6–8 mm long.